1988
DOI: 10.1111/j.1524-4725.1988.tb03480.x
|View full text |Cite
|
Sign up to set email alerts
|

Microcystic Adnexal Carcinoma: A Case Showing Eccrine Duct Differentiation

Abstract: Microcystic adnexal carcinoma (MAC) is a cutaneous neoplasm comprised of pilar and sweat duct structures. Characteristically, the ductal structures manifest immunoreactivity for carcinoembryonic antigen (CEA) on immunostaining. The case of MAC discussed here shows strictly sweat duct differentiation. Using a monoclonal antibody to salivary mucin (CF-1) that is specific for eccrine duct, we identify the neoplastic structures to be of eccrine sweat duct histogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…However, studies investigating the utility of immunohistochemistry in the diagnosis of microcystic adnexal carcinoma are few and restricted both in the spectrum of lesions and antibodies studied (Table 1). [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Thus, even though immunohistochemical comparisons of microcystic adnexal carcinoma vs infiltrative basal cell carcinoma and desmoplastic trichoepithelioma exist in the published literature, they are confined to a single stain; and to date, only two studies employing a panel of immunohistochemical stains are performed. 17,19,21,23,24,26 In addition, a comparative study of microcystic adnexal carcinoma with squamous cell carcinoma particularly squamous cell carcinoma with ductal differentiation has not, to our knowledge, been reported previously.…”
mentioning
confidence: 99%
“…However, studies investigating the utility of immunohistochemistry in the diagnosis of microcystic adnexal carcinoma are few and restricted both in the spectrum of lesions and antibodies studied (Table 1). [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Thus, even though immunohistochemical comparisons of microcystic adnexal carcinoma vs infiltrative basal cell carcinoma and desmoplastic trichoepithelioma exist in the published literature, they are confined to a single stain; and to date, only two studies employing a panel of immunohistochemical stains are performed. 17,19,21,23,24,26 In addition, a comparative study of microcystic adnexal carcinoma with squamous cell carcinoma particularly squamous cell carcinoma with ductal differentiation has not, to our knowledge, been reported previously.…”
mentioning
confidence: 99%
“…Some tail‐like appendages of the nests and ducts resemble tadpole formations seen in syringoma 3,4,13 . Both components are present in variable proportions, but some cases display only one 11,23,24 . Peri‐ and intraneural invasion is a common and characteristic finding 3,6 .…”
Section: Discussion and Reviewmentioning
confidence: 96%
“…Controversies are centered on the histogenesis of MAC; it has been reported that MAC shows follicular differentia tion [3], sweat gland differentiation [2][3][4]. or dual differen tiation [1,6,7], We used antibodies against CEA, S-100 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Histo genesis of MAC has caused much controversy, since sev eral studies using microscopic, immunohistochemical or electron-microscopic techniques have revealed that MAC exhibits sweat gland differentiation [2][3][4], pilar differentia tion [5] or both [1.6, 7|. Only a few immunohistochemical examinations using antibodies against hard keratins or cytokeratins have been performed [8,9).…”
Section: Introductionmentioning
confidence: 99%